Single-Axis Solar-Powered Water Quality Monitoring with Internet of Things - Mohd, Ahmad Syakir Iman; Mohamad, Khairul Anuar (Evolution in Electrical and Electronic Engineering, 2025)
This project focuses on the design and implementation of a single-axis solar-powered water quality monitoring system integrated with Internet of Things (IoT) technology to enable real-time data collection, transmission, and analysis of key water parameters. The aim of this project is to provide an efficient, reliable, and sustainable solution for monitoring water resources, particularly in remote or off-grid areas where traditional manual sampling methods are time-consuming, costly, and often result in delayed responses. The system incorporates a single-axis solar tracking mechanism designed to maximize energy generation by continuously adjusting the position of the solar panel toward the sun throughout the day. During testing at UTHM lake, the solar tracking system successfully produced an output power of 21.04 W, demonstrating its ability to supply continuous energy to power the IoT-based sensors. These sensors recorded key water quality parameters, including pH levels ranging from 6.29 to 6.39, turbidity measured at 42.5 NTU, and water temperature between 28.3°C and 32.3°C. The collected data was transmitted in real time to a cloud platform for storage, monitoring, and analysis, enabling timely detection of changes in water quality. The findings of this project demonstrate that the system can operate effectively under actual environmental conditions, offering a practical and environmentally friendly solution for continuous water quality monitoring and proactive water resource management.